PENGEMBANGAN MEDIA POP UP BOOK PADA PEMBELAJARAN IPA KELAS IV DI SD NEGERI 4 TANJUNG TEBAT - Reza Anggraeni; Jayanti Jayanti; Adrianus Dedy (JS (JURNAL SEKOLAH), 2022)
Abstract: From the results of observations and interviews with the fourth grade guardian of SD Negeri 4 Tanjung Tebat, it was stated that the use of pop-up book media for animal life cycle materials had never been done or did not exist. Judging from the lack of existing teaching facilities or materials, and the learning has not been linked to the pop-up book media, so that it can lead to a lack of student knowledge about the use of animal life cycle materials. The purpose of this study was to determine the development of pop-up media in the fourth grade science learning at SD Negeri 4 Tanjung Tebat. The method used in this study is research and development (RnD) with the limits of expert judgment and practicality. The validation of the developed media was carried out with media experts, linguists, and material experts. While the practicality of the media was tested on teachers and students. Data was collected using questionnaires and documentation techniques, while data analysis techniques used percentages. The results of the expert's assessment showed that the media pop-up book with a percentage of 89.11%. Thus, it can be concluded that the development of pop-up book media on animal life cycle materials for Class IV SD is included in the very valid or very feasible category. From the results of practitioners, namely teachers and students, a percentage of 90.62% was obtained. Thus, it can be concluded that the practicality of pop-up book media in Class IV Elementary School learning is included in the very practical category.Keywords: Media, Pop-Up, ScienceAbstrak: Dari hasil observasi dan wawancara dengan Wali Kelas IV SD Negeri 4 Tanjung Tebat menyatakan bahwa penggunaan media pop-up book materi daur hidup hewan  belum pernah dilakukan atau memang belum ada. Dilihat dari kekurangan sarana atau bahan ajar yang ada, serta pembelajarannya belum mengaitkan dengan media pop-up book, sehingga dapat menyebabkan minimnya pengetahuan siswa terhadap penggunaan materi daur hidup hewan. Tujuan penelitian ini adalah untuk mengetahui pengembangan media pop-up pada pembelajaran IPA Kelas IV di SD Negeri 4 Tanjung Tebat. Metode yang dipakai pada penelitian ini yakni research and development (RnD) dengan batas penelitian penilaian ahli dan praktikalitas. Validasi media yang dikembangkan dilakukan dengan ahli media, ahli bahasa, dan ahli materi. Sedangkan praktikalitas media di ujikan kepada guru dan siswa. Pengumpulan data dilakukan dengan Teknik angket dan dokumentasi, sedangkan teknik analisis data menggunakan persentase. Hasil penilaian para ahli menunjukkan bahwa media pop-up book dengan persentase sebesar 89,11%. Dengan demikian, dapat disimpulkan bahwa pengembangan media pop-up book pada materi daur hidup hewan Kelas IV SD termasuk dalam kategori sangat valid atau sangat layak. Dari hasil praktisi yaitu guru dan siswa diperoleh persentase sebesar 90,62%. Dengan demikian, dapat disimpulkan bahwa kepraktisan media pop-up book pada pembelajaran Kelas IV Sekolah Dasar termasuk dalam kategori sangat praktis.Kata Kunci: Media, Pop-Up, IPA